2017
DOI: 10.1017/jns.2017.5
|View full text |Cite
|
Sign up to set email alerts
|

Overweight dogs are more likely to display undesirable behaviours: results of a large online survey of dog owners in the UK

Abstract: Much of the global canine population is now overweight, and this can adversely affect health, lifespan and quality of life. Undesirable behaviours are also common in pet dogs, and these can adversely affect welfare, as well as being stressful to owners. However, links between obesity and behavioural disorders have never previously been explored. An online survey was conducted between June and August in 2014, coinciding with the broadcast of a National UK television programme, exploring dog health, welfare and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
36
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 23 publications
(37 citation statements)
references
References 17 publications
1
36
0
Order By: Relevance
“…The main questions considered in the current study are those regarding activity, breed and other signalment details. The data on exercise have also been used in a separate study examining the associations between exercise and overweight status ( 6 ) , whilst the questions relating to behaviour are reported elsewhere ( 7 ) .…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The main questions considered in the current study are those regarding activity, breed and other signalment details. The data on exercise have also been used in a separate study examining the associations between exercise and overweight status ( 6 ) , whilst the questions relating to behaviour are reported elsewhere ( 7 ) .…”
Section: Methodsmentioning
confidence: 99%
“…small, medium or large), according to The UK KC classification ( 4 ) . Unlike for the related papers ( 6 , 7 ) , data from dogs under 2 years of age were eligible for inclusion in the analysis for this study. Outcome variables of interest included: frequency of exercise outside of the home/garden (see categories above); walked once per d or more (yes/no); duration of usual exercise (see categories above); and met UK KC guidelines of exercise for that breed (yes/no).…”
Section: Methodsmentioning
confidence: 99%
“…Additionally, dogs that are more fearful and show aggression to strangers or other dogs (and therefore might not return to the owner when called), are less likely to be allowed offleash. A recent study found that such dogs were also more likely to be overweight, perhaps because their owners do not allow their dogs to exercise outside the house and garden, or restrict their freedom if they do (108).…”
Section: Discussionmentioning
confidence: 99%
“…For exercise duration, the question asked was ‘Each time you exercise your dog how long is it for?’ and respondents could select: ‘over an hour’, ‘30 minutes to an hour’, ‘11–30 minutes’ and ‘0–10 minutes’. The same data on exercise were also used for a separate study examining activity patterns amongst different dog breeds ( 13 ) , whilst the questions relating to behaviour are reported elsewhere ( 14 ) .…”
Section: Methodsmentioning
confidence: 99%
“…Sex and neuter status were binary and age continuous as whole years. For breed, those that had previously been identified as significantly associated with overweight status (at P  < 0·0017) in a study using the same data ( 14 ) were initially included, each coded as a separate variable (whereby 1 = from that breed and 0 = not from that breed). An initial multiple regression model was constructed including all variables, and this was refined in a forwards and backwards stepwise fashion, so as to optimise the fit of the model and take account of covariance.…”
Section: Methodsmentioning
confidence: 99%